Effectiveness of Problem-Focused Coping Strategies on the Burden on Caregivers of Hemodialysis Patients - Ghane; Ashghali Farahani; Seyedfatemi; Haghani (Kashan University of Medical Sciences, 2016)
Background Studies have shown that family caregivers of hemodialysis patients experience high levels of burden. However, these caregivers are often neglected, and no studies are available on the effectiveness of coping strategies on the burden of care among these caregivers. Objectives This study aimed to examine the effectiveness of problem-focused coping strategies (communication skills, anger management, and deep breathing) on the burden on caregivers of hemodialysis patients. Patients and Methods A randomized controlled clinical trial was conducted on 76 family caregivers of hemodialysis patients referred to Shahid Hasheminejad hemodialysis center in Tehran, Iran. The subjects were equally allocated into two groups of 38. Through a coin-tossing method, caregivers of patients who referred on even or odd days of the week were randomly assigned into the intervention group or the control group, respectively. The intervention group received four training sessions on problem-focused coping strategies, but the control group did not receive any intervention. Both groups answered the caregiver's burnout inventory at the start and six weeks after the last educational session. Descriptive statistics, chi-square, Fisher's exact test, independent-samples t-test, and Mann-Whitney U test were used to analyze the data. Results The majority of caregivers (54%) were in the age range of 35 - 55 years, female (68.4%), and married (70%). No significant difference was found between the baseline mean caregivers' burden scores of the intervention and control groups (88.56 ± 11.74 vs. 84.97 ± 15.13, P = 0.308). However, the mean caregivers' burden in the intervention group decreased, and the two groups were significantly different at the end of the study (58.77 ± 6.64 vs. 87.84 ± 11.74, P < 0.001). Conclusions The current study showed the effectiveness of problem-focused coping strategies on reducing the burden on caregivers of hemodialysis patients. Authorities and policymakers in the healthcare system are responsible for developing strategies to integrate educational programs, such as the program implemented in the current study, into the country's healthcare system.